Conector de aço para ligações entre painéis de madeira laminada colada cruzada e entre painéis de madeira laminada colada cruzada e laje de concreto pré-fabricado - Fernando Murilo Gontijo Ramos (2023)
The wood is still being rediscovered as an excellent construction material in Brazil, and mainly, as one of the most ecological material.In the production scene of sustainable building scenario, the constructive system that uses wooden panels – widely used in Europe, United States and Canada – called as Glued Laminated Timber (GLT) and Cross Laminated Timber (CLT), occupies a prominent place, especially for the possibility of using the wood from planted forests.This work developed a steel connector,, to be used in the connections of CLT panels with CLT panels, and prefabricated concrete slabs with CLT panels and therefore, to make an experimental evaluation, through push-out test evaluation, which means shear testing both single and double shear, torsion and flexion evaluations. All that to assert and verify the structural behavior of these connectors in situations of service. The results of these tests will be compared with the results obtained using the equations proposed in EUROCODE design standards 4 and 5, and in test standard EN 26891, 1991.In a first step, it was introduced the general idea of the constructive system in which the connectors are inserted, its constituent elements and its connections. Afterwards the behavior of steel shear connectors in conection to CLT panels, was evaluated in an experimental way using CLT panels and prefabricated concrete slabs. These panels were fabricated (with Eucalyptus Grandis) and analysed in the Laboratory of Experimental Analysis of Structures(LAES) and Advanced Research Center for Wood, Furniture and New Materials (CEPAM III), both from the Structural Engineering Department of Universidade Federal de Minas Gerais – UFMG. In this second stage, the results of the experiment with CLT panels manufactured industrially in the country were evaluated, through advanced manufacturing technology, using Pinus Taeda wood, the experimental results were compared with the methodology recommended by EUROCODE 5 which proved to be conservative and that, in general, we can deduce that the strength properties of the mixed connections of wood and concrete should be evaluated by tests.